Analysis of the role of inter-nanowire junctions on current percolation effects in silicon nanonet field-effect transistors. (June 2020) - Cazimajou, T.; Mouis, M.; Legallais, M.; Nguyen, T.T.T.; Ternon, C.; Salem, B.; Ghibaudo, G.
Abstract: In this paper, we compare the evolution with temperature of the experimental characteristics of Nanonet-based Field-Effect Transistors, with a modelling of carrier transport in the percolating regime. The main electrical parameters of Nanonet-based Field-Effect Transistors that featured different nanowire densities and source-drain distances were extracted from static measurements at different temperatures. The temperature dependence of low field mobility and threshold voltage was explained by the temperature activated behaviour of inter-nanowire junctions, and the activation energy dispersion of individual junctions. A Monte-Carlo simulation of Nanonet FET in the shape of a random percolating network of resistances and thermally activated junctions was used to confirm the influence of activation energy dispersion on low field mobility. The simplest model which was able to capture experimental trends consisted in a bimodal distribution of activation energies, with a subset of non-thermally activated junctions (resistive junctions) while other junctions were thermally activated (energy barriers at the junctions).